FRI0344 Predictors of early relapse in patients with non-infectious mixed cryoglobulinemia vasculitis: results from the french nationwide cryovas survey. (23rd January 2014) - Terrier, B.; Marie, I.; Launay, D.; Plaisier, E.; de Saint-Martin, L.; Chiche, L.; Kahn, J.-E.; Rullier, P.; Mariette, X.; Cacoub, P.; ,
Abstract : Background: Data on the outcome of patients treated for non-infectious mixed cryoglobulinemia vasculitis (CryoVas) in the era of hepatitis C virus screening are lacking. Although in most patients, induction therapy leads to complete or partial remission, relapses in patients with non-infectious mixed CryoVas remain a major problem. Objectives: To identify potential predictors of early relapses occurring with the first 12 months in patients with non-infectious mixed CryoVas. Methods: Eighty-one French centers of Internal Medicine, Nephrology, Rheumatology, Hematology, Dermatology and Neurology from University and general hospitals have included 242 patients with non-infectious mixed CryoVas diagnosed between January, 1995 and July, 2010. Patients exhibiting complete or partial remission after induction therapy and followed-up for at least 12 months were analyzed for predictors of early relapses, i.e. occurring within the first 12 months. All variables with a p value <0.2 in the univariate analysis have been included in a multivariate logistic regression model. Results: 106 women and 39 men (sex ratio F/M 2.7), mean age 61.2±11.8 years, were included. Forty out of the 145 patients (28%) experienced an early relapse within the first 12 months of follow-up. Relapses occurred after a median time of 9.5 months (3-12). These relapses involved the skin in 75%, the joints and peripheral nerve in 28%, the kidneys in 25% and the gastrointestinal tract in 5%. Baseline factors associated with an early relapse in univariate analysis were purpura (P=0.006), cutaneous necrosis (P=0.006) and articular involvement (P=0.025). No biological feature was associated with an early relapse. In multivariate analysis, these factors remained significantly associated with an early relapse: purpura [OR 3.35 (1.02-10.97), p=0.046], cutaneous necrosis [OR 4.46 (1.58-12.57), p=0.005] and articular involvement [OR 2.20 (1.00-4.78), p=0.048]. The factors associated with an early relapse during the follow-up, i.e., the treatments used and the response to therapy, in univariate analysis were the use of corticosteroids alone (P=0.026) and the absence of achievement of complete clinical or immunological response (P=0.034 and 0.0005, respectively). In contrast, the initial dosage of corticosteroids and the use of plasmapheresis were not associated with lower rate of early relapse. In multivariate analysis, the only factor associated with an early relapse was the absence of complete immunological response [OR 0.07 (0.01-0.51), P=0.009]. Conclusions: In patients with non-infectious mixed cryoglobulinemia vasculitis, main predictors of early relapses after initial remission are purpura, cutaneous necrosis and articular involvement. The use of combination therapy associating corticosteroids and immunosuppressive agents and the achievement of a complete immunological response were associated with lower rates of early relapse. These findings may help adapt treatment strategies. Disclosure of Interest : None Declared